0414 Results From an On-Road Driving Performance Study In Non-elderly And Elderly Healthy Subjects with Dual Orexin Receptor Antagonist Lemborexant. (27th April 2018) - Vermeeren, A; Vuurman, E; Jongen, S; Van Leeuwen, C; Van Oers, A; Ramaekers, J; Murphy, P; Moline, M; Perdomo, C; Pinner, K
Abstract: Introduction: Sedating CNS-active drugs are typically studied for the potential to impair next-morning driving. Data from an on-road driving performance study are presented for lemborexant (LEM), a dual orexin receptor antagonist under development for insomnia disorder. Methods: Randomized, double-blind, 4-period, incomplete crossover design. Healthy subjects (n=24 non-elderly, n=24 elderly; 26M, 22F) received placebo (P), zopiclone 7.5mg (Z; positive control), and 2 of 3 LEM doses (2.5/5/10mg). P and LEM were taken for 8 consecutive nights; Z was dosed on Night 1 and Night 8 with P on Nights 2–7. The standardized 1-hr on-road driving tests on Day 2 (D2) and Day 9 (D9) started ~9h post dose. Standard deviation of lateral position (SDLP in cm) was the primary endpoint. Results: All 48 subjects completed the study. Assay sensitivity was demonstrated, as for Z vs P, the 95% CI upper bound was >2.4cm (standard threshold for impairment) at both D2 and D9. Additionally, mean SDLP for Z vs P and symmetry analyses of subjects with SDLP difference in Z vs P >2.4cm vs <2.4cm were statistically significant at D2 and D9 ( P <0.01). For each LEM dose vs P, the 95% CI upper bound was <2.4cm. No mean SDLP for LEM vs P was significant for any dose on D2 ( P >0.05) or D9 ( P >0.05). Symmetry analyses were not statistically significant for any LEM dose on D2 or D9 ( P >0.05). Results were similar in age and sex subgroups. No serious or severe adverse events (AEs) were reported. AEs of somnolence were reported more frequently after LEM 10mg than LEM 2.5 and 5mg administration. Conclusion: As measured by SDLP and at the doses tested, lemborexant did not impair driving performance after either single (Day 2) or multiple (Day 9) dose administration. These results warrant continued testing of the efficacy and safety of LEM for the treatment of insomnia disorder. Support (If Any): Eisai, Inc and Purdue Pharma L.P.